The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/dc.22810
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing in malignant melanoma

Abstract: Molecular testing of cancers to determine therapeutic eligibility is now standard of care and has changed the practice of pathology. Recent advances in the treatment of metastatic melanoma with BRAF and KIT inhibitors have increased the demand for molecular testing in melanoma. Furthermore, rapid progress is being made in determining potential new targets, mechanisms of resistance, and developing additional rationally designed therapies. The likely consequence will be a significant expansion of molecular testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 95 publications
1
25
0
1
Order By: Relevance
“…The majority (~90%) of patients with early detected melanoma are curable; however, the efficiency of clinical drugs in the treatment of patients with advanced metastatic melanoma is <20% (2), and the 5-year survival rate is <5%, with a median survival time of only 2-8 months (3,4). Numerous studies have confirmed that the poor prognosis of malignant melanoma is primarily attributable to the high incidence of distant metastasis and a strong capacity for invasion (5)(6)(7). Therefore, the development of more effective therapies for the inhibition of metastasis presents a challenge for the treatment of malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…The majority (~90%) of patients with early detected melanoma are curable; however, the efficiency of clinical drugs in the treatment of patients with advanced metastatic melanoma is <20% (2), and the 5-year survival rate is <5%, with a median survival time of only 2-8 months (3,4). Numerous studies have confirmed that the poor prognosis of malignant melanoma is primarily attributable to the high incidence of distant metastasis and a strong capacity for invasion (5)(6)(7). Therefore, the development of more effective therapies for the inhibition of metastasis presents a challenge for the treatment of malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…17 The histologic subtype that more often shows BRAF mutations is superficial spreading melanoma; the acral, mucosal, uveal, and lentigo maligna variants usually have a wild-type BRAF. 17 Of the 3 RAF genes that participate in the ERK1/2 signal transduction cascade (ie, ARAF, BRAF, and CRAF), BRAF is the one that is most frequently affected in cutaneous melanoma. This is probably because, unlike ARAF and CRAF, BRAF requires the phosphorylation of only a single amino acid within the activation loop to become active.…”
Section: Mutations Of Proteins Integral To the Erk1/2 Cascade In Cutamentioning
confidence: 99%
“…17 Also, Sanger sequencing still seems to have some advantages over mutation-specific assays. Although the sensitivity of the cobas 4800 test for the detection of the BRAF V600E has been shown to be comparable with, or even better than, that of Sanger sequencing, the latter also allows for the detection of BRAF mutations other than V600E.…”
Section: Mutations Of Other Proteins Of the Erk1/2 Cascadementioning
confidence: 99%
See 2 more Smart Citations